Pengaruh Kompetensi, Independensi, dan Profesionalisme terhadap Kemampuan Auditor Badan Pemeriksa Keuangan Provinsi Sumatera Selatan dalam Mendeteksi Fraud - M. Faishal Akbar Athaillah; Sarikadarwati; Desri Yanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of competence, independence, and professionalism on the ability of auditors of the Badan Pemeriksa Keuangan (BPK) Perwakilan Provinsi Sumatera Selatan to detect fraud. Fraud is an act that has a major impact on state finances and requires serious attention from government auditors. The research method used is a quantitative method with a survey approach through a questionnaire distributed to 40 auditors of the BPK Perwakilan Provinsi Sumatera Selatan. Data analysis was performed with multiple linear regression using the SPSS application. The results showed that competence and independence partially and simultaneously had no significant positive effect on the auditor's ability to detect fraud. Meanwhile, professionalism partially and simultaneously has a significant positive effect on the auditor's ability to detect fraud. These findings confirm the importance of increasing competence, maintaining an independent attitude, and auditor professionalism in order to strengthen fraud detection in the public sector.